2017
DOI: 10.1016/j.virusres.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Picornaviral polymerase structure, function, and fidelity modulation

Abstract: Like all positive strand RNA viruses, the picornaviruses replicate their genomes using a virally encoded RNA-dependent RNA polymerase enzyme known as 3Dpol. Over the past decade we have made tremendous advances in our understanding of 3Dpol structure and function, including the discovery of a novel mechanism for closing the active site that allows these viruses to easily fine tune replication fidelity and quasispecies distributions. This review summarizes current knowledge of picornaviral polymerase structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 94 publications
1
84
0
Order By: Relevance
“…The GII.17 isolate displays evolutionary rates at least 1 order of magnitude higher than those seen with GII.4, further establishing the role of the RdRp in the emergence of new epidemic strains (Chan et al, 2015). The hypothesis that RdRp-driven genetic diversity is vital for viral fitness and pathogenesis is not unique to norovirus, and has been well documented for other virus families such as Picornaviruses (Vignuzzi et al, 2006;Peersen, 2017). Consistent with reports on the poliovirus polymerase, Arias et al reported a high-fidelity MNV polymerase variant associated with the I391L mutation (Arias et al, 2016).…”
Section: Role Of Norovirus Rdrp In Pathogenesis and Epidemiologymentioning
confidence: 80%
“…The GII.17 isolate displays evolutionary rates at least 1 order of magnitude higher than those seen with GII.4, further establishing the role of the RdRp in the emergence of new epidemic strains (Chan et al, 2015). The hypothesis that RdRp-driven genetic diversity is vital for viral fitness and pathogenesis is not unique to norovirus, and has been well documented for other virus families such as Picornaviruses (Vignuzzi et al, 2006;Peersen, 2017). Consistent with reports on the poliovirus polymerase, Arias et al reported a high-fidelity MNV polymerase variant associated with the I391L mutation (Arias et al, 2016).…”
Section: Role Of Norovirus Rdrp In Pathogenesis and Epidemiologymentioning
confidence: 80%
“…As mentioned before, the Lys159 residue is located in motif F of the RdRp, which has been reported to play an important role in NTP binding during viral RNA synthesis (10). NTP binding is known to be a major fidelity checkpoint, and point mutations in this motif could annihilate polymerase activity or slow down catalysis (18). Mutating this lysine residue to an arginine or methionine resulted in reduced polymerization efficiency, which is likely the consequence of less efficient access of the incoming NTPs to the active site of RdRp.…”
Section: Discussionmentioning
confidence: 96%
“…(19,20), the residue Ala239 participates in a tetrahedral hydrogen bond network. This network helps position the Asp238 residue to the active site of the RdRp, providing a direct link between the properly positioned NTP and a set of structural interactions that promote catalysis by stabilizing the closed active site (18). Based on structural analysis of CVB3 polymerase, the residues Lys159 and Ala239 are closely located in the channel of the incoming NTP.…”
Section: Discussionmentioning
confidence: 99%
“…A number of culture-independent methods exist now to characterize the novel viruses and their genes. Biochemical assays for RdRp, proteases, helicases, capsids, and internal ribosome entry sites all exist and synthetic biology allows for easy cloning from a database to test these new proteins found through metagenomics (Ladd Effio et al, 2016;O'Donoghue et al, 2012;Peersen, 2017). Profiling known functions across the new viral species, such as RNA binding strength and sequence specificity of novel RNA phage proteins related to MS2 phage or viral protease specificity and kinetics, might be a place to start (O'Donoghue et al, 2012).…”
Section: Experimenting With Functionmentioning
confidence: 99%